2023
DOI: 10.1055/s-0043-1766096
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Müller-Weiss Disease

Abstract: Müller-Weiss disease (MWD) is the result of a dysplasia of the tarsal navicular bone. Over the adult years, the dysplastic bone leads to the development of an asymmetric talonavicular arthritis with the talar head shifting laterally and plantarly, thus driving the subtalar joint into varus. From a diagnostic point of view, the condition may be difficult to differentiate from an avascular necrosis or even a stress fracture of the navicular, but fragmentation is the result of a mechanical impairment rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(85 reference statements)
1
0
1
1
Order By: Relevance
“…Moreover, regression analysis revealed a positive correlation between midfoot abduction and postoperative pain after midfoot arthrodesis (P = .007). These results are consistent with those of Harnroongroj et al 14 When reviewing previous MWD literature and scrutinizing their illustrations, we found that most researchers focused more on restoring the medial longitudinal arch, 4,10,17,19 medial column length, 10,31 hindfoot alignment, 5,18,24 and perinavicular arthrodesis through malreduction, 3,11,13,20 while overlooking midfoot abduction. The clinical AOFAS and VAS scores in the reduction group were better than those in the malreduction group (all P < .05), implying that the pain was caused not only by the degeneration of the involved joints, but also by impaired biomechanics, such as the midfoot abduction deformity represented by the TMT1dp, leading to an uneven load distribution on the foot (Figures 1, 5, and 6).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, regression analysis revealed a positive correlation between midfoot abduction and postoperative pain after midfoot arthrodesis (P = .007). These results are consistent with those of Harnroongroj et al 14 When reviewing previous MWD literature and scrutinizing their illustrations, we found that most researchers focused more on restoring the medial longitudinal arch, 4,10,17,19 medial column length, 10,31 hindfoot alignment, 5,18,24 and perinavicular arthrodesis through malreduction, 3,11,13,20 while overlooking midfoot abduction. The clinical AOFAS and VAS scores in the reduction group were better than those in the malreduction group (all P < .05), implying that the pain was caused not only by the degeneration of the involved joints, but also by impaired biomechanics, such as the midfoot abduction deformity represented by the TMT1dp, leading to an uneven load distribution on the foot (Figures 1, 5, and 6).…”
Section: Discussionsupporting
confidence: 90%
“…Müller-Weiss disease (MWD) is characterized by progressive foot deformity and medial navicular subluxation. Contrary to the findings of previous studies, 5,10,22 MWD is not as uncommon, particularly according to foot and ankle surgeons. MWD is more prevalent among women and often occurs bilaterally, with its primary symptom being chronic pain in the peri-navicular joints during weightbearing.…”
Section: Introductioncontrasting
confidence: 99%
“…El diagnóstico se realiza mediante una radiografía simple de pie con carga, observando la deformidad en varo del retropié, escafoides en forma de "coma" por la constante compresión, [7][8] divergencia astrágalo -calcáneo disminuida, inex minus que hace referencia al primer metatarsiano más corto de lo habitual.…”
Section: Diagnóstico -unclassified